Associations Between Serum IL‐17A, Renal Function and Diabetic Retinopathy in Type 2 Diabetes Mellitus: Evidence From a Chinese Han Population - Wensu Wang; Yan Huang; Jianguo Shen; Li Jin; Zhuo Chen (Endocrinology, Diabetes & Metabolism)
ABSTRACT Background Evidence suggested that IL‐17A was associated with renal function in type 2 diabetes. We used ultra‐sensitive measurement to detect the concentration of IL‐17A in human peripheral blood and explored the association of IL‐17A with diabetic kidney disease (DKD). Methods We recruited 138 participants from the Shanghai Diabetes Institute Inpatient Database of Shanghai Jiao Tong University Affiliated Sixth People's Hospital. Eighty‐four individuals diagnosed as DKD were cases, and 54 type 2 diabetes individuals without DKD or diabetic retinopathy (DR) were controls. The concentration of serum IL‐17A was detected by the High Sensitivity Immunoassay Quantitative Kit. Data was analysed by SAS. Results The concentration of serum IL‐17A in our population ranged from 0.07 pg/mL to 2.96 pg/mL with the median of 0.502 pg/mL. Our results suggested that the level of serum IL‐17A in DKD case group was higher than in the control (P unadjusted = 0.0496, P adjusted = 0.0298). And serum creatinine, eGFR, ACR were used as indicators of renal function. Serum creatinine and ACR were positive correlated with the level of serum IL‐17A (P adjusted = 0.0148; P adjusted = 0.0369), while eGFR showed a negative correlation (P adjusted = 0.0167). Additionally, the level of serum IL‐17A was also significantly higher in DR case group compared with the control group (p = 0.0224). Conclusion Serum IL‐17A level is associated with renal function decline and diabetic retinopathy in patients with type 2 diabetes in a Chinese Han population. Our results suggested that IL‐17A may be a potential biomarker of DKD and DR.